The Motive Bases for the Formation and Activation of the State-Creating Patriotism of the Nation Based on the Strategiology of the State Development - Karpinskyi Borys A.; Karpinska Olena B. (Problemi Ekonomiki, 2023)
The purpose of the article is to allocate and systematize scientific views on the motives that become an effective strategiologic trend in the formation and development of the State, synthesized and manifested through the State-Creating Patriotism of the Nation (SCPN) with its dominants: qualitative; and quantitative (tax-based). It is emphasized and substantiated that the motives have their own characteristic hierarchy within the system of manifestation of both SCPN and strategiology of development, since they are oriented towards a particular person or the international community of States in general. It is emphasized that in order to select and analyze in detail the manifestation of characteristic motives as to the considered issues of creation of the State and their further activation, it is necessary to carry out a gradation regarding the classification of citizens according to the fundamental provisions of sociology, in particular, through subcultures (i. e., groups of people who recognize a certain system of values and are united are united according to certain social characteristics). It is substantiated that the SCPN represents all that the people in general and every citizen in particular do in the interests of creating an independent, sovereign, civilized State. It is noted that taxes are a quantitative feature and a measure of the motive-actual SCPN to specify the real participation (current and future) of taxpayers in the formation of the financial component of life provision and further development of the State. The author emphasizes that a taxpayer does not just pay taxes, but by doing so, creates his/her own civilized State - for himself/herself and the descendants. It is through a purposeful strategiologic activation of the motiveness of SCPN, changing only by 1% the level of shadowing of the world economy, that it is possible to provide up to $ 350 billion of additional tax revenues to the States’ budget. The motive-based mechanism for activating the process of creation of the State based on the paradigm of the SCPN and the strategiology of the State development is highlighted. The motivational fundamentality of activating the quantitative approach of the SCPN as an effective strategiologic direction of development of each State ensures, in particular: growth of budget revenues; reduction of both the level of the shadow economy due to the both activation of patriotic sentiments of taxpayers and the costs of tax administration; accumulation of more effective opportunities for the State to resolve and ensure the constitutional rights of citizens